Pengaruh Kemiskinan Dan Laju Jumlah Penduduk Terhadap Pertumbuhan Ekonomi Indonesia - Maulana, Yoga Tri; Cahya, Refin Dwi; Desmawan, Deris (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2022)
The purpose of this study is to analyze the impact of poverty and population ratio on economic growth from 2015 to 2019. This study uses a quantitative approach. research based in Indonesia. The method used in this study is multiple linear regression panel data. The results of this study indicate that poverty and population have no significant effect on economic growth. These results indicate that there are still many factors that can significantly affect economic growth.